Studies on the ecology and systematics of the diatoms (Bacillariophyta) from some South Africa rivers - Archibald, Robert Eldred Mostert (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1969)
This report contains the results of some ecological and systematic studies on the diatoms from the Vaal Dam catchment area in the Transvaal, and the Bloukrans River in the Eastern Cape Province. In Part 1 the effects of high concentrations of nitrogen were studied in relation to the composition of the diatom associations. Water samples from four stations on the Bloukrans River were analysed chemically at certain intervals during the months of April and August 1967. Diatom samples collected from these stations at the beginning and end of each of these sampling periods were subjected to a "Thomasson Analysis" to determine the relative densities of the various species in the diatom associations. A statistical analysis of the results reflected a poor but positive correlation between the two variables, i.e. high numbers of nitrogen heterotrophic Nitzschiae were correlated with high concentrations of nitrogen, while low numbers were correlated with low concentrations. Part 2 presents the results of the ecological studies on the diatom associations of the Vaal Dam Catchment Area. In this section the diatom associations from each sampling point or station were subjected to a "Thomasson Analysis" to determine the relative densities of the different species in the associations. Employing already known correlations between environment and association, the results of this analysis were discussed and the ecological conditions for each sampling station were assessed. The associations were similar in composition over the entire catchment area, and indicated on the whole water of good quality. Points of pollution were detected, but were generally localised and the effects of the pollution were soon removed. Only the Waterval River showed evidence of more constant pollution. The associations provided evidence for some seasonal variation in their composition. Finally in Part 3 the systematics and taxonomy of the diatoms in the Vaal Dam catchment area are discussed. References are made to the original and more recent descriptions of each species found in this study, and a list of synonyms is given wherever 'possible. Comments on the systematics, taxonomy and autecology of each species are given, and the distribution of the species in South Africa and the Vaal Dam catchment area is discussed. A number of species, varieties and forms have been recorded for the first time in South Africa. During the course of this study 20 species have been described as new to science; the descriptions of some have been published, while the descriptions of the others will be published formally in the future. All species described as new or having interesting features are illustrated in the plates.
Keywords: Diatoms -- Ecology -- South Africa; Diatoms -- Classification; Aquatic ecology -- South Africa